1984
DOI: 10.1007/bf00286586
|View full text |Cite
|
Sign up to set email alerts
|

The current state of research with peripheral tissues in Huntington disease

Abstract: Huntington disease is a neurological autosomal dominant disease of unknown origin and the search for a suitable diagnostic marker has been extended to the peripheral tissues. It is generally believed that a membrane defect exists in Huntington disease although the evidence is controversial. It is the aim of this review to examine the validity of these claims for each of the peripheral tissues and techniques involved, and it is not intended to include all other aspects of research into Huntington disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 170 publications
0
7
0
Order By: Relevance
“…In addition to protein misfolding, mitochondrial defects, and oxidative stress, cell death is one of the major events reported in neuronal and peripheral pathologies associated with mutant huntingtin in HD [6, 8, 30, 46, 8186]. A recent study reported the association between mutant HTT and cell death pathways, particularly evident in cardiac tissue [34].…”
Section: Huntington’s Disease-induced Cardiac Disease and Cell Deathmentioning
confidence: 99%
“…In addition to protein misfolding, mitochondrial defects, and oxidative stress, cell death is one of the major events reported in neuronal and peripheral pathologies associated with mutant huntingtin in HD [6, 8, 30, 46, 8186]. A recent study reported the association between mutant HTT and cell death pathways, particularly evident in cardiac tissue [34].…”
Section: Huntington’s Disease-induced Cardiac Disease and Cell Deathmentioning
confidence: 99%
“…Meanwhile, the differences between HD patients and controls which have been ob served with other methods have also been the subject of contradictory reports [3], which lends support to our contention that the ad mittedly attractive theory of a generalized membrane defect must be reconsidered. For early diagnosis of HD ESR is entirely use less.…”
Section: Discussionmentioning
confidence: 80%
“…The investigations carried out to date have produced contradictory results in different laboratories [3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with HD exhibit peripheral immune changes, including circulating and tissue-based immune cells [ 12 ]. In R6/2 mice, activated T cells can be identified by the expression of cell surface markers, such as OX40, CD40L and CD25 [ 56 ].…”
Section: Spleen As Immune Tissuementioning
confidence: 99%
“…Apart from the neuronal impairment of HD, some studies have described pathological phenotypes in the peripheral tissues of HD patients, including altered glucose homeostasis [ 8 ] and weight loss [ 9 ]. Other studies have analyzed the particular changes in blood cells such as erythrocytes [ 10 ] and lymphocytes [ 11 ], as well as in fibroblasts [ 12 ], immune blood cells [ 13 , 14 ], the pancreas [ 15 ], the heart [ 16 , 17 ], the retina [ 18 ], the liver [ 19 ], the kidney [ 20 ], pericytes and the blood–brain barrier [ 21 ] from HD patients. The models can aid understanding of how HTT affects peripheral tissues and contributes to disease progression.…”
Section: Introductionmentioning
confidence: 99%